Efficient Noise-Vibration-Harshness Modelling of Servo- and Traction Drives. Issue 21 (2016) - Kotter, P.; Zirn, O.; Wegener, K.
Abstract: This paper advances a system-simulation based universal modelling approach for NVH-simulation of electric drives. The main idea is to use commercial FE-tools for model parametrisation and implement generic reduced electrodynamic and acoustic models in a system-simulation environment. The NVH-calculation itself is done in a system-simulation framework, which can be easily coupled with control and machine models for electric drives. The proposed approach is worked out in detail. As a first example, the simulation procedure is performed for an outrunner traction drive of electrified foldable scooters.